Rancang Bangun Aplikasi Pengenalan Kapal Perang Indonesia Menggunakan Augmented Reality - Rizki Maulana; ali suryaperdana agoes (Journal of Information Technology, 2022)
The Unitary State of the Republic of Indonesia (NKRI) is one of the large maritime countries where the ocean area is almost twice the land area within the Republic of Indonesia. With conditions like this, the Republic of Indonesia has a strong Navy which of course has a reliable fleet of warships for defense and securing state sovereignty. Indonesian warships have their own charm according to their uses, in carrying out their roles and functions. One of the warships owned by Indonesia such as KRI 365 Diponegoro, KRI 331 R.E Martadinata, KRI 403 Nagapasa which is equipped with various kinds of weaponry. In Indonesia, not everyone knows what the shape and use of warships is like. Therefore, to make it easier to find out information about Indonesian warships, the author makes scientific learning about warships using Augmented Reality (AR) technology on the introduction of warships in Indonesia.